Breaking Bad: An Assessment of Ophthalmologists' Interpersonal Skills and Training on Delivering Bad News - Fuerst, Nicole M.; Watson, Jessica S.; Langelier, Nicole A.; Atkinson, R. Egen; Ying, Gui-Shuang; Pan, Wei; Palladino, Vincent; Russell, Collin; Lin, Vanessa; Tapino, Paul J.; O'Brien, Joan M. (Journal of Academic Ophthalmology, 2018)
Purpose This article aims to assess ophthalmologists' practice patterns, experiences, and self-perceived skills when delivering bad news to patients and to compare this to patients' experience and preferences in receiving bad news from ophthalmologists.Design/Methods This is a prospective cross-sectional survey study of two populations: (1) Attending ophthalmologists and current ophthalmologists-in-training (N = 202) at accredited ophthalmology residency programs in the United States and Canada. (2) Patients (N = 151) 18 years of age and older at a single academic center who had received bad news from their ophthalmologist. An e-mail was sent to ophthalmology department chairs and resident program directors requesting that they distribute an online survey to their faculty, fellows, and residents. Patients were recruited from the clinics at an academic center and completed a self-administered survey before their scheduled appointments. Both populations were surveyed on their experience in breaking and receiving bad news, respectively. Questions were rated on a standard five-point Likert scale, and mean score was calculated for statistical comparison. The primary outcome variable was the quantitative rating (Likert scale 1–5) of physicians' communication skills when delivering bad news from physicians and patients' responses.Results Patients rated their physicians higher than physicians rated themselves with regard to ability to deliver bad news (mean score of 4.23 vs. 3.48, p < 0.01). Multivariate analysis showed frequent delivery of bad news (mean score of 3.66 for once per day, 3.53 for per week, 3.40 for once per month, and 3.22 for once per year, linear trend; p = 0.004) and years of practice were associated with better self-perceived ability to deliver bad news (mean score of 3.75 for ≥15 years, 3.48 for <15 years, and 3.30 for residents/fellows, linear trend; p < 0.001). Having received formal training in breaking bad news was associated with better perceived ability score, yet not statistically significant (3.51 vs. 3.39, p = 0.31). Most patients (97.5%) and physicians (92.1%) believe delivering bad news can be taught.Conclusion Physicians and patients agree that skills of delivering bad news can be learned. Patients are less critical of their physicians' ability to deliver bad news than physicians are themselves. Further study of best methods to deliver bad news is clearly indicated for the field of ophthalmology.
Keywords: breaking bad news; core competencies; medical education